Experiencing Tanzania: Reflections of a Medical Service Learning Trip Through the Eyes of Aspiring Physicians - Dietrich Büsselberg (11008857) (2018)
This book reflects the views of a group of students selected for a service trip to Tanzania about what they experienced on their journey. The essays, written by students and local professionals, may give an impression not only of Tanzania and its rich environment but also of the challenges the country faces. Flipping through the pages and pictures should also give you a sense of the beauty of the country and the people of Tanzania. Other Information License: https://creativecommons.org/licenses/by/4.0/ See book on publisher’s website:https://doi.org/10.5339/wcm-q.9789927129643